Peran Kepuasan Kerja Sebagai Mediasi Pada Gaya Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan - Nanda Marinda; Yateno; Fitriani (Universitas Muhammadiyah Metro, 2026)
This research aims to find out whether leadership style influences employee performance. To find out whether compensation affects employee performance. To find out whether leadership style influences employee job satisfaction. To find out whether compensation has an effect on employee job satisfaction. To find out whether employee job satisfaction influences employee performance. To find out the role of job satisfaction on leadership style and employee performance. To find out the role of job satisfaction on compensation and employee performance. Based on the sampling technique used, namely probability sampling with a saturated sampling category. The number of samples used was 60 respondents. Data collection in this research used observation, interviews and questionnaires. The data analysis technique used in this research is testing instrument requirements consisting of validity and reliability tests, testing analysis requirements consisting of normality tests and linearity tests, hypothesis testing using path analysis, T Test (Partial Test) and Coefficient of Determination (R Square). The results of this research show that (1) leadership style has a positive effect on employee performance. (2) compensation has a positive effect on employee performance. (3) leadership style has a positive effect on job satisfaction. (4) compensation has a positive effect on job satisfaction. (5) job satisfaction has a positive effect on employee performance.